Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae) - Pereira-Filho, José Moisés B.; Saturnino, Regiane; Bonaldo, Alexandre B. (Zootaxa, 2018)
Five new Brazilian species of the spider genus Attacobius Mello-Leitão, 1925 are described: A. demiguise n. sp. (based on male and female) and A. carimbo n. sp. (male), both from State of Pará; A. thalitae n. sp. (male) from the State of Minas Gerais; A. lauricae n. sp. (male) from State of Tocantins; and A. tremembe n. sp. (female) from State of Piauí. The males of A. luederwaldti (Mello-Leitão, 1923) and A. verhaaghi Bonaldo & Brescovit, 1998, and the females of A. uiriri Bonaldo & Brescovit, 2005 and A. blakei Bonaldo & Brescovit, 2005, are described for the first time. Additionally, new records of A. attarum (Roewer, 1935), A. carranca Bonaldo & Brescovit, 2005, A. kitae Bonaldo & Brescovit, 2005 and A. tucurui Bonaldo & Brescovit, 2005 are given.